68Gallium-DOTATATE PET in meningioma: A reliable predictor of tumor growth rate?. Issue 7 (9th February 2016) - Sommerauer, Michael; Burkhardt, Jan-Karl; Frontzek, Karl; Rushing, Elisabeth; Buck, Alfred; Krayenbuehl, Niklaus; Weller, Michael; Schaefer, Niklaus; Kuhn, Felix P.
Abstract: Background: DOTATATE-based radionuclides have added new options in the diagnosis and treatment of meningiomas; however, a reliable predictor of tumor growth has still not been established. Methods: We analyzed 64 meningiomas imaged with 68 Ga-DOTATATE PET. Tumor growth rates were calculated by volumetric analysis of sequential MRI scans. Maximums of standardized uptake values (SUVmax ) were correlated with tumor growth and covariates. Results: World Health Organization (WHO) grades I and II meningiomas showed a correlation of SUVmax and tumor growth rate (meningiomas limited to the intracranial compartment: r = 0.757, P < .001, and transosseous growing meningiomas: r = 0.819, P = .024). SUVmax was significantly higher and the slope of the linear regression significantly steeper in transosseous compared with intracranial meningiomas (both P < .001). The association remained significant in multivariate analysis, and the prediction of tumor growth rate was independent of WHO grade. Anaplastic meningiomas showed no significant correlation of SUVmax and tumor growth. Conclusions: 68 Ga-DOTATATE PET is a reliable predictor of tumor growth in WHO grades I and II meningiomas and provides additional information to conventional cross-sectional imaging modalities. Hence, 68 Ga-DOTATATE PET can assist in selecting the time point for treatment initiation. Furthermore, meningiomas with fast tumor growth and transosseous expansion elicit the highest DOTATATE binding; therefore, they might be especially suited for DOTATATE-based therapy.